Analisis Variasi Kecepatan Putaran Pisau Pemarut Kelapa dengan Mesin Motor Jupiter Z1 113 CC - Ariswanto, Muhamad Riswan; Saleh, Agus (Universitas Muhammadiyah Tangerang, 2024)
Coconut is one of the resources that has high economic value in various industries. Although it has many benefits, the coconut grating process is still often done manually, resulting in low production capacity and taking a long time. With the rapid development of technology, the coconut grating machine is the result of technology to crush coconut meat into small grains. In this design, the coconut grating machine uses a 113 CC Jupiter Z1 motor equipped with adjustable speed variations. Therefore, this design aims to analyze the effect of variations in knife rotation speed on the coconut grating machine on time efficiency in the coconut grating process, and design a coconut grating machine equipped with variations in knife rotation speed. The making of this coconut grating machine is intended to be more efficient and is expected to increase the productivity of coconut grating as needed.